English language teachers’ speaking assessment beliefs and practices in Malaysian secondary schools - Jamil, Nur Zaimah; Barghi, Ali Hamed; Nimehchisalem, Vahid; Mohd Ali, Afida (Academy Publication, 2025)
This study examines the correlation between Malaysian secondary school English teachers’ speaking assessment beliefs and their actual classroom practices within a classroom-based assessment framework. Adopting a quantitative research approach, data were collected from 98 teachers via a survey, and correlational analysis was employed to examine the strength, direction, and significance of the relationship between their beliefs and practices. The findings indicate that while teachers generally believe speaking assessment is important for developing students’ communication skills, their actual practices do not always match these beliefs. A statistically significant moderate positive correlation was found between teachers’ beliefs about speaking assessment and their frequency of using it; teachers who attached more importance to it, tended to use it more in practice. The results highlight the need for focused professional development and clearer guidelines to assist teachers in aligning teachers’ assessment beliefs and practices. This alignment will promote more effective and consistent use of speaking assessments in the classroom.